Modeling digital wayang kulit based on traditional wayang kulit characteristics - Ahmad, Jasni; Jamaludin, Zulikha (2012)
Threatened with imminent extinction, Wayang Kulit (WK) or shadow play has been designated as a Masterpiece of Oral and Intangible Heritage of Humanity on 7th November 2003 by UNESCO.In an attempt to further preserve and safe guard this unique heritage of WK, this study proposes a model of a digital version of WK (DWK).We believe, by doing so, it could help in preserving the traditional WK since it can be used in other domain (such as education) apart from leisure purposes.The model takes into account the evolution and revolution of the traditional WK. Also, for each WK figure, its characteristics and functions are compared and analysed to determine its dominance in the play.This paper also proposes a feature-characteristic matrix as a part of the component of the DWK’s model.